Hi
I am trying to solve for r in the following:
F=P(1+r)^t
I've got it to: log(t) =log(F/P) / Log(1+r)
can someone please show me the step by step stages to make r the subject? How do i remove the logs?
Many thanks
H
This is wrong. log(a^b)= b log(a), not "log(b)log(a)". From
F/P= (1+ r)^t, taking the logarithm of both sides give log(F/P)= t(log(1+ r)) so that log(1+ r)= (1/t) log(F/P)= log((F/P)^{1/t}). Now take the "anti-log" (exponential) of both sides to get 1+ r= (F/P)^{1/t} and so r= (F/P)^{1/t}- 1, exactly what Prove It said.
can someone please show me the step by step stages to make r the subject? How do i remove the logs?
Many thanks
H